The transformation of political communication : continuities and changes in media and politics - Negrine, Ralph M. (Basingstoke [England] ; New York : Palgrave Macmillan, 2008)
The relationship between politics and the media is continually evolving. This book explores the technological, political and social forces that affect the practice of political communication throughout the world today. Offering a critical, historical approach, this book is for all students interested in the communication of politics.
Introduction.- The Transformation and Professionalization of Political Communication: what does it mean?.- Media and Politics: how and why political parties communicate politics.- The Transformation of Political Parties organizational change and communication technologies.- The Transformation of Political Parties organizational change and professional advisers in the communication of politics.- Political Actors: transforming practices.- Transforming Government Communication.- The Transformation of Political Communication: the global context.- The Internet: transforming political communication?.- Conclusion: the transformation and professionalization of communication and its impact on politics.- Bibliography.
Includes bibliographical references (p. 205-219) and index.
Keywords: Communication -- Political aspects; Communication in politics